Mineral Composition of Leaves of some Forest Trees Grown on Alkali Soils - Garg, V. K.; Khanduja, S. D. (Indian Forester, 1979)
Mineral composition of leaves of six forest tree species growing on an alkali soil showed highest concentration of cations in Terminalia and lowest in Callistemon. Sodium concentration was highest in Cassia leaves. The ratio of leaf - Na to total sum of cations showed preferential accumulation of Na by Callistemom in relation to other species. All the species were found to grow well with pH 9.6 to 9.8 in their root zone.